1986
DOI: 10.1111/j.1365-2125.1986.tb02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐adrenergic receptors in human blood vessels.

Abstract: The evidence for the presence of postjunctional alpha 1- and alpha 2-adrenoceptor subtypes in human blood vessels is reviewed. Experiments in healthy subjects are described that show that alpha 1- as well as alpha 2-adrenoceptor mediated vasoconstriction contribute to vascular smooth muscle tone and that adrenaline and noradrenaline have similar affinities for each subtype. In addition, evidence is presented for a preferential intrajunctional location of alpha 1-adrenoceptors and a preferential extrajunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…In human vasculature, locally released norepinephrine (by lower body negative pressure and by tyramine infusion) has a different functional effect than infused norepinephrine. 36 Apparently the released norepinephrine preferentially activates postsynaptic a,-receptors, whereas norepinephrine infusion also activates vasoconstrictive extrajunctional a 2 -receptors. 37 This functional difference in the patterns of receptor activation with endogenous versus exogenous norepinephrine permits the postulation of different mechanisms by which physiological vasoconstriction may have a larger effect than the vasoconstriction with infused norepinephrine.…”
Section: Discussionmentioning
confidence: 98%
“…In human vasculature, locally released norepinephrine (by lower body negative pressure and by tyramine infusion) has a different functional effect than infused norepinephrine. 36 Apparently the released norepinephrine preferentially activates postsynaptic a,-receptors, whereas norepinephrine infusion also activates vasoconstrictive extrajunctional a 2 -receptors. 37 This functional difference in the patterns of receptor activation with endogenous versus exogenous norepinephrine permits the postulation of different mechanisms by which physiological vasoconstriction may have a larger effect than the vasoconstriction with infused norepinephrine.…”
Section: Discussionmentioning
confidence: 98%
“…AI immediately reduced CBF and CVC, with little doubt as a result of a-adrenoreceptor-induced vasoconstriction in the skin (Edholm et at. 1956;Whelan, 1967;Van Brummelen et al 1986). These decreases in CBF and CVC were accompanied by a transient decline in skin temperature (n.s.)…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, although there is now convincing evidence that post-junctional vascular a2-adrenoceptors are involved in the regulation of vascular tone in humans (Van Brummelen et al, 1986) stimulation of the 'classical' vascular a1-adrenoceptors appears to remain the major determinant of systemic vascular resistance. It is therefore conceivable that, at least at high infusion rates, a-methylnoradrenaline loses its relative a2-vs a1-selectivity and may also stimulate vascular a1-adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that pre-junctional a2-adrenoceptors are involved in the regulation of noradrenaline release in man (Brown et al, 1985;Jie et al, 1987) and that post-junctional a2-adrenoceptors may contribute to the regulation of human peripheral vascular tone (van Brummelen et al, 1986). In addition it has been reported that post-junctional a2-adrenoceptor mediated vasoconstriction is enhanced in essential hypertension (Bolli et al, 1984).…”
Section: Introductionmentioning
confidence: 99%